Pengaruh Customer Relationship Management dan Kualitas Layanan Terhadap Kepuasan Nasabah PT. Clipan Finance Bandar Lampung - Putra, Hafiz Fernanda; Negara, Tri Lestira Putra Warga (Jurnal EMT KITA, 2024)
In facing increasingly fierce competition in the era of globalization, especially in the motor vehicle financing sector, companies must focus on effective marketing strategies. Customer Relationship Management (CRM) is the main basis for creating various product references for customers. This research aims to analyze the influence of Customer Relationship Management (CRM) and Service Quality on customer satisfaction at PT. Clipan Finance Bandar Lampung. This research used quantitative methods involving 61 respondents as samples. Data analysis was carried out using a multiple linear regression model, by calculating the coefficient of determination and testing the hypothesis using the t test and F test. The research results show that the t test (partial) confirms that Customer Relationship Management (CRM) and Service Quality have a positive and significant influence on satisfaction customers. Meanwhile, the results of the F test state that together, Customer Relationship Management (CRM) and Service Quality have a significant effect on customer satisfaction. Analysis of the coefficient of determination concludes that Customer Relationship Management (CRM) and Service Quality jointly influence customer satisfaction at PT. Clipan Finance Bandar Lampung.